Clinical Outcomes of Very Short Term Dual Antiplatelet Therapy in Patients With or Without Diabetes Undergoing Second-Generation Drug-Eluting Stents: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Liang, Xi-Ying; Li, Yan; Qiao, Xuan; Zhang, Wen-Jiao; Wang, Zhi-Lu (Frontiers in Cardiovascular Medicine, 2021)
Background: Patients with diabetes represent 20–30% of the population considered for percutaneous coronary intervention (PCI) and associate with more deleterious clinical outcome, which requires the optimal strategy of dual antiplatelet therapy (DAPT). The meta-analysis aims to compare clinical outcomes between very short (1–3 months) and standard (12 months) DAPT after implanting the second-generation drug-eluting stents in patients with or without diabetes following PCI. Methods and Analysis: PubMed, Embase, Web of Science, Ovid, Cochrane Library, and ClinicalTrials.gov were searched for studies comparing the very short term and standard DAPT in patients with or without diabetes following PCI. Risk ratio with 95% confidence intervals was used to evaluate the pooled effect of discontinuous variables, and the pooled analyses were performed with RevMan 5.3 and Stata SE 14.0 software. Results: A total of 38,864 patients were randomized to the very short term DAPT (N = 19,423) vs. standard DAPT (N = 19,441). Among them, 11,476 patients were diabetes and 27,388 patients were non-diabetes. The primary outcome of the net adverse clinical event (NACE) was significantly lower in diabetic patients with very short term DAPT (risk ratio 0.72, 95% CI 0.60–0.88, p = 0.0009). The same result was also found in the major cardiac or cerebrovascular events (MACCEs) (0.87, 0.78–0.98, p = 0.03). The risk of major or minor bleeding was significantly reduced in very short term DAPT regardless of the diabetes statue (0.69, 0.52–0.93, p = 0.01 in the diabetic group, and 0.50, 0.39–0.63, p <0.0001 in the non-diabetic group). There was no statistical difference in the incidence of major bleeding, all-cause death, cardiac death, myocardial infarction, definite or probable stent thrombosis, and stroke between the very short term DAPT (1–3 months) and standard DAPT (12 months) in patients with or without diabetes. Conclusion: The very short term DAPT can significantly reduce the risk of the NACE and MACCE in patients with diabetes compared to standard DAPT. Meanwhile, the very short term DAPT can also reduce the incidence of major and minor bleeding without increasing the risk of ischemia in patients with or without diabetes (Registered by PROSPERO, CRD42020192133). Systematic Review Registration:https://www.crd.york.ac.uk/prospero/, Identifier: CRD42020192133.